Mechanical deterioration of ACSR conductors due to forest fires. - Sung-Duck Kim
Considerations for the remaining life of the aluminum stranded conductors steel reinforced (ACSR) in transmission lines have become gradually important to hold the reliability and the stability of the electric power supply. The useful life of the ACSR exposed to the atmosphere for a long period may be dependent on deterioration caused by such factors as atmospheric corrosion, galvanic corrosion, crevice corrosion, or fatigue corrosion. Forest fires for any overhead transmission lines built nearly on the ridge of the mountains may significantly reduce to the mechanical strength of the ACSR and lead to failure or accident. In this paper, material and mechanical deterioration performances of ACSR due to forest fires are presented through several sample tests. Data analysis for tension load and extension of ACSR after blazed are reported.
Keywords: ACSR conductors; Accident; Aluminum stranded conductors steel reinforced; Atmospheric corrosion; Crevice corrosion; Failure; Fatigue corrosion; Forest fires; Galvanic corrosion; Material deterioration; Mechanical deterioration; Mechanical strength; Overhead transmission lines; Power supply reliability; Power supply stability; Remaining life; Sample tests